Progression of Benign Breast Tumors: A Review of Differential Expression of BRCA1 - Warda Fatima; Unzila Yasin (International Health Review, 2021)
Benign breast tumors, a group of heterogeneous disorders, have a high incidence in females which is the effect of multiple environmental and genetic factors. Some notable genetic factors include the involvement of the highly penetrant BRCA1 gene and its major interactions with other genetic activators. BRCA1’s interaction with certain proteins, such as 53BP-1 and ATM kinases, is initiated through the phosphorylation of their respective domains to create varied complexes with different functions. Consequently, BRCA1/BACH complex formation, in particular, helps in DNA repair processes. When this formation mutates, it can produce severe benign breast tumors. On the other hand, TP53 gene mutation also causes high damage to breast epithelia, irrespective of its interaction with BRCA1 function. BARD1 protein is also known to assist BRCA1 in maintaining its phenotype during the entire process of repair. These complex formations reveal the dual functioning of BRCA1 in relation to different proteinaceous entities as a tumor suppressor gene and a breast disease causing gene. Thus, this study focuses on BRCA1 mutation, its interaction with other genes, and its role in the DNA repair processes.